2010
DOI: 10.1007/s00439-010-0907-3
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal recessive mental retardation: homozygosity mapping identifies 27 single linkage intervals, at least 14 novel loci and several mutation hotspots

Abstract: Mental retardation (MR) has a worldwide prevalence of around 2% and is a frequent cause of severe disability. Significant excess of MR in the progeny of consanguineous matings as well as functional considerations suggest that autosomal recessive forms of MR (ARMR) must be relatively common. To shed more light on the causes of autosomal recessive MR (ARMR), we have set out in 2003 to perform systematic clinical studies and autozygosity mapping in large consanguineous Iranian families with non-syndromic ARMR (NS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 30 publications
1
35
0
Order By: Relevance
“…[8][9][10][11][12] In affected children from consanguineous families, autosomal recessive (AR) inheritance is common; 13 however, congenital disorders with ID constitute an important medical problem because they represent a challenge in diagnosis, high prevalence and life-long care that most of these patients need. 14 A recent review suggests that ARID is not rare, and in outbred populations as many as 13-24% of ID may be due to AR genes, 13 and identifying the underlying genetic cause is an important issue in clinical genetics.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] In affected children from consanguineous families, autosomal recessive (AR) inheritance is common; 13 however, congenital disorders with ID constitute an important medical problem because they represent a challenge in diagnosis, high prevalence and life-long care that most of these patients need. 14 A recent review suggests that ARID is not rare, and in outbred populations as many as 13-24% of ID may be due to AR genes, 13 and identifying the underlying genetic cause is an important issue in clinical genetics.…”
Section: Introductionmentioning
confidence: 99%
“…Although functional considerations and empirical data from mouse models suggest that most gene defects are inherited as recessive disorders, 1,4,5 a recent study suggests that autosomal dominant de novo mutations are most prevalent. 6 Until now, 26 significantly linked non-specific intellectual disability of autosomal recessive inheritance (NS-ARID) loci were described, [7][8][9][10] and only 10 genes (six of them located in described regions) were identified: PRSS12 (OMIM#606709, on 4q26, former MRT1), CRBN (OMIM#609262, on 3p26, former MRT2), CC2D1A (OMIM#610055, on 19p13.12, former MRT3), ST3GAL3 (OMIM#606494, on 1p34.3), GRIK2 (OMIM#138277, on 6q16, former MRT6), TUSC3 (OMIM#601385, on 8p22, former MRT7), ZNF26 (no OMIM#, on 19q13.2), TRAPPC9 (OMIM#613192, on 8q24, former MRT13), ZCH14 (OMIM# 613279, on 14q31.3), and TECR (MIM*610057 on 19p13.12) (Figure 1). 1,[11][12][13][14][15][16][17][18][19] Taking into account that over 90 genes are responsible for only about 40% of X-chromosomal recessive ID cases, and that about half of the estimated 22 000 human genes are expressed in the brain, the total number of ARID genes may run into the hundreds.…”
Section: Introductionmentioning
confidence: 99%
“…1 Considering the heterogeneity observed in previous linkage studies, and the fact that the so far identified genes do not account for a significant fraction of NS-ARID cases, systematic approaches are the most promising strategy to identify further genes. 7,8,10 Large consanguineous families provide enough information to map loci, based on analysis in a single family and thus represent the best starting point. We present here the results of the homozygosity mapping in a series of 64 Syrian multiplex consanguineous families with NS-ARID.…”
Section: Introductionmentioning
confidence: 99%
“…2,4 Although the homozygous regions of some reported ARID genes (MED13L, COQ5, ZCCHC8) overlap with this locus, 3 to the best of our knowledge, the present locus has not been previously linked to ID. Up to now, 40 loci for ARID (MRT1-40) have been registered in the OMIM database.…”
Section: Discussionmentioning
confidence: 66%
“…Up to now, we have reported several novel MRT loci (mental retardation loci) and genes for recessive cognitive disorders. [2][3][4] Here, we present a single homozygous interval on chromosome 12q24, with LOD score 43, which is a new MRT locus for ARID. Targeted exome sequencing within this interval revealed a nonsense variant in the CLIP1 gene (MIM 179838), which encodes a member of the microtubule (MT) plus-end tracking proteins.…”
Section: Introductionmentioning
confidence: 99%